Civil Aviation Occurrences in Indonesia - Agus Pramono; Jason H Middleton; Carlo Caponecchia (Journal of Advanced Transportation)
Globally, civil air traffic has been growing rapidly in recent years, and with this growth, there has been a considerable improvement in air safety. However, in Indonesia, the recent rate of incidents and accidents in aviation is far higher than the global average. This study aims to assess civil aviation safety occurrences in Indonesia and, for the first time, to investigate factors contributing to these occurrences within commercial Indonesian aviation operations. In this study, 97 incident/accident investigation reports published by the Indonesian National Transportation Safety Committee between 2007 and 2015 were analysed. The most common occurrences involved Runway Excursions, Loss of Control In-Flight, and Controlled Flight into Terrain. In terms of the likelihoods of the occurrences and the severity of consequences, Runway Excursions were more common while Loss of Control In-Flight and Controlled Flight into Terrain events were more severe and often involved fatalities. In Indonesia, Runway Excursions were usually nonfatal and comprised 45% of the occurrences for commercial flights, compared to 34% globally. Further, in this study, weather and Crew Resource Management issues were found to be common contributing factors to the occurrences. Weather was a contributing factor for almost 50% of the occurrences involving Indonesian commercial flights. Adverse weather contributed to Loss of Visual Reference for visual flight operations in mountainous areas, which contributed to the majority of Indonesian fatal accidents. The combination of Indonesian monsoon climate and mountainous weather characteristics appears to provide many risks, mitigation of which may require specialist pilot training, particularly for multicrew aircraft. In identifying the main contributing factors, this study will hopefully provide motivation for changes in training and operations to enhance future aviation safety in Indonesia.